Saúde mental e racismo: a atuação de um Centro de Atenção Psicossocial II Infantojuvenil - David, Emiliano de Camargo (2018)
This paper considers the assumption that racism, in relation to power and the attempt to keep privileges, produces subjectivities and might generate psychic suffering, affecting (also) black children and teenagers and their territories. The aim of this research was to discuss the relationship between psychosocial care and racism through the perspective of those who work at a juvenile Psychosocial Care Centre II (CAPSij). In order to do that, an institutional perspective of analysis was favoured, one that sees racism as an institution, as a logic of production and reproduction of social interactions. To achieve the objectives, a review of the literature about psychology and racial interactions was carried out, highlighting the relationship between insanity and the black population, as well as the relationship between racism and health care inequities and the empiric study in a CAPSij. The study used the following procedures: participant observation; reading of medical records; partaking in meetings and staff interviews, with the intention of: characterizing possible psychic sufferings related to racism; using colour/race as an item in the planning of Singular* Therapeutic Projects (STP) for users under care; psychosocial interventions to fight racism. The material collected was organized into two thematic axes: the first, based in two cases brought by professionals, discusses how the team think the relationship between psychic suffering and racism and how they develop their intervention; the second approaches the dimensions of the service organization and of the political-institutional sphere. The ongoing interventions and therapeutic projects at the CAPSij suggest that the ethical-political dimension of the anti-asylum fight already takes into consideration the effects of racism within their commitment with the freedom practices and refusal of exclusion and violence processes. However, they also suggest that seeing the effects of racism as an anti-asylum issue, which is being called a CAPS assembly, might augment the power of actions in health care that contributes to the promotion of racial equity and to the deinstitutionalisation of racism